(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
In its third decade, the State University of Distance Education of Costa Rica (UNED-C.R.) face -as one of its challenges- the increase of students participation in research. This paper aims to show how it is possible for UNED to establish students´ networks for research by means of ample profiles. Through E-Mirador -a research Project- 46 students participated in this experience during 2011 and 2012. From Marta Alles´concepts, related to ample profile, vital local connections of students were considered in order to give evidence of how social and cultural context might make them likely to participate in groups and networks of investigation. It was considered among the variables elements such as: ample academic background (second major, technical background, etc.) technological and scientific profile (publication of articles, participation in academic activities and projects). From the total of 46, only 9 students met these requirements. Their networks and vital connections were also analized. Partial results have been reached so far. It is possible to give evidence that these 9 students have wide and important habilities and connections in their environments, giving thus multiplicity of knowledge and disciplines that may enhance their opportunities to participate in networks. In the mean time, some of these students are trying this metodology in order to build research networks with local impact.